Pengelolaan Kegiatan Ekstrakurikuler Tari dalam Mengembangkan Kecerdasan Kinestetik Menggunakan Metode Add-On (Linked) di SD Negeri 07 Kabupaten Lebong - Mely Ledyta; Dwi Anggraini; Osa Juarsa (Universitas Bengkulu, 2021)
This research was carried out to find out the extracurricular management of dancing in developing chinestetics intelligence by using Add-On (Linked) method at SD Negeri 07 Lebong Regency. This research was in descriptive qualitative method. The subject of the study amounted to 9 students of the dance members of SD Negeri 07 Lebong Regency .The instruments in this research were guided interview and guided observation. The analysis of data was done by analyzing all data gathered from interview, observation, and documentation in the form of dancing video. The obtained data was analyzed through reducing data, collecting data, and giving conclusion. Credibility testing was through increased persistence, triangulation and member check. The result of the research showed that (1) management related to the planning of extracurricular dance activities is to prepare dance, determine the schedule of practice and make disciplines that are conveyed orally, 2) management related to the implementation of extracurricular dance activities, namely, the use of Add-On (Linked) method in each exercise. This method is implemented gradually so that students can easily memorize dance moves consisting of 17 movements, 3) management related to evaluation is to use four aspects to see the development of kinesthetic intelligence of students. There is an improvement in every aspect of dance practice so that students have been able to develop their kinesthetic intelligence well. The conclusion of this study is (1) on the planning of researchers adding Add-On (Linked) method and planning to practice as many as 6 meetings within 2 weeks (2) on the implementation process of using Ad-On (Linked) method in dance practice has a good effect in developing students kinesthetic intelligence, while (3) evaluation needs to be done to see the development of kinesthetic intelligence of students every time exercise.